The Effect Of Life Review Therapy On Increasing Self-Esteem In The Elderly With Depression - Yuldensia Avelina; Yosefina Dhale Pora; Wihelmus Nong Baba (Babali Publisher, 2023)
Introduction: Depression is one of the psychiatric problems experienced by the elderly and can reduce the quality of life of the elderly. Elderly with depression will have low self-esteem. Low self-esteem results in withdrawal from new activities. Depression in the elderly is higher in the elderly who live in nursing homes compared to the elderly who live in the community and psychological interventions are still low to overcome depression and increase the self-esteem of the elderly. This study aims to determine the effect of life review therapy on increasing the self-esteem of elderly people with depression in the Social Welfare Section of the Padu Wau Maumere Elderly Social Welfare. Method: The type of research used is a quasi experiment with a one group pretest-posttest research design. The number of samples is 36 people, using consecutive sampling. The instruments used in this study were the short questionnaire Geriatric Depression Scale (GDS) with 15 questions in the Indonesian version to measure depression in the elderly and the Rosenberg-Self Esteem questionnaire to measure self-esteem with 10 questions in the Indonesian version. The life review therapy intervention was given in 4 sessions, namely the experiences of childhood, adolescence, adulthood and the elderly. Data analysis used the Wilcoxon test. Results: The results showed that before being given life review therapy most of the respondents experienced moderate depression as much as 83.3% and most of them experienced low self-esteem as much as 83.3%. after being given life review therapy the results showed that most respondents experienced no depression as much as 72.2% and most experienced high self-esteem as much as 61.1%. The results of the Wilcoxon test showed that there was an effect of life review therapy on increasing the self-esteem of the elderly with depression as evidenced by the p value (0.000) <α (0.05) so that the alternative hypothesis was accepted. Conclusion: The conclusion in this study is that there is a significant effect of life review therapy in increasing the self-esteem of the elderly with depression in the Social Welfare Section of the Padu Wau Maumere Elderly Social Welfare. The results of this study imply the importance of providing psychosocial therapy for the elderly who experience depression so that it can have an impact on increasing the self-esteem and quality of life of the elderly. Keywords: word; Depressions, Elderly, Self Esteem, Therapy Life Review